Actitudes de la mujer ante el embarazo - Albarracín, Martha D. de (1966)
The authors investigate the correlations between the acceptance and refusal attitudes in regard to pregnancy and absence o presence of distocic factors during childbirth. In order to evaluate it, they apply a projective test visual stimulation which tries to show the woman's atiudes in regard o pregnancy in several vital situations, trying to test its correlations with the pregnancy and childbirth caracteristics.